The Experience of a Mother Who Has Been Malnourished - Deswita, Deswita; Fadilah, Nurul; Sari, Ira Mulya (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Malnutrition is a health issue that contributes to infant morbidity and mortality. In order for toddlers' growth and development to proceed normally, it is crucial that mothers surmount these obstacles.Aims: The aim of this research is to find out how the experience of the mother in treating poor nutrition babies in the work area of Public Health Centre Air Dingin City Padang.Methods : This study employs qualitative techniques and a phenomenological approach. In-depth interviews serve as the data collection method. The number of participants in this study was four mothers selected via purposive sampling based on the criterion of having successfully treated malnourished infants to adequate nutrition. The collected data consists of a verbatim transcription of the results of the interview, which is then analyzed using the collaizi technique.Results: This study's findings include mothers' knowledge of how to treat malnourished infants, the food consumed by children, mothers' positive conduct during babysitting, emotional regulation during infant care, and support for mothers during infant care.